The weight loss bible - Hall, Joanna (Kayle Cathie Limited, 2005)
A definitive guide to losing weight for all ages and body shapes, including custom-tailored exercise routines and healthy menus. Achieve your ideal weight now with this no-nonsense guide from fitness expert Joanna Hall. Her book works by customizing diets and exercise plans to meet your needs, ensuring that you lose your target weight in effective, sustainable programs. She first helps you decide on a realistic plan that suits your body shape, your previous diet history, and your current motivation. She then provides you with the knowledge to understand your body and the key guiding principles that will help you stay slim on a permanent basis. With tasty, nutritious eating plans, and fat-burning muscle-sculpting exercises, this is an action plan that will bring out your best.